Fototerapi pada Dermatologi Anak - Wibisono Nugraha; Endra Yustin Ellistasari (PT Dexa Medica, 2023)
Phototherapy is a non-ionizing ultraviolet (UV) radiation therapy used as a treatment for several medical conditions. The mechanism of action of phototherapy is to act as antiproliferative, induce apoptotic, and provide immunosuppressive effect. Several therapeutic modalities that can be used as alternative therapy in children include NB-UVB, BB-UVB, ultraviolet A, PUVA, and excimer laser. Phototherapy in children is indicated especially in diseases such as psoriasis, atopic dermatitis, vitiligo, pityriasis lichenoides, and mycoses fungoides. The use of phototherapy has indications, contraindications, dose, and side effects that should be considered when choosing appropriate phototherapy in children. Common side effects are erythema, xerosis, burning sensation, and itching. Several groups of patients with refractory complaints are advised to use additional phototherapy modalities, either as monotherapy or in combination with topical and systemic therapy.